Refugees as a new emigration channel from Tajikistan to Western and Eastern Europe - A. Kh. Rakhmonov (Управление)
The article examines the situation with refugees during the civil war in Tajikistan after the collapse of the USSR. The factors and scale of refugees and features of asylum seekers from Tajikistan are considered. The scale and prospects for the development of the flow of refugees and asylum seekers from Tajikistan to Western and Eastern Europe are investigated. Every year, a huge number of people leave their homes due to armed conflicts, wars, poverty, and persecution on various grounds. One of the reasons for the refugees influx from Tajikistan to other countries is the civil war in the republic. After the collapse of the USSR, a power struggle between nationalists and Islamists began in Tajikistan that led to a civil war. The emergence of the refugees flow from Tajikistan to other countries is related with the civil war in the republic. Another reason is the ban by the Tajik authorities of two major opposition organisations – the Group of 24 and the Islamic Renaissance Party of Tajikistan (IRPT). Among the Tajik political refugees who received asylum in European countries, there are also former migrant workers who worked in Russia. Deportations, decline in earnings after the 2015 currency crisis, and tightening of Russia’s migration policy towards migrants from Tajikistan forced some migrants to reorient themselves in other countries, primarily in European countries, the United States and Canada. There are cases of deliberate destruction of their passports by Tajik migrants when moving to Germany, followed by an appeal to the authorities under the guise of refugees from Afghanistan (since both Tajiks and Afghans speak Farsi (Dari)) to obtain refugee status and corresponding benefits in Germany. Among asylum seekers from Tajikistan in European countries, political asylum is the most popular. The purpose of the article is to identify trends and prospects for the development of asylum as a new emigration channel from Tajikistan to the countries of Western and Eastern Europe.